A Double-Blind, Randomized Multicenter Trial Comparing Duloxetine with Placebo in the Management of Diabetic Peripheral Neuropathic Pain - Raskin, Joel; Pritchett, Yili L.; Wang, Fujun; D'Souza, Deborah N.; Waninger, Amy L.; Iyengar, Smriti; Wernicke, Joachim F. (Pain medicine (Malden, Mass.), 2005)
ABSTRACT Objective.  Assess efficacy and safety of duloxetine, a selective serotonin and norepinephrine reuptake inhibitor, on the reduction of pain severity, in patients with diabetic peripheral neuropathic pain (DPNP). Methods.  This was a multicenter, parallel, double‐blind, randomized, placebo‐controlled trial that enrolled 348 patients with pain due to peripheral neuropathy caused by type 1 or type 2 diabetes mellitus. Patients (N = 116 per group) were randomly assigned to receive duloxetine 60 mg once daily (QD), duloxetine 60 mg twice daily (BID), or placebo, for 12 weeks. The primary outcome measure was the weekly mean score of 24‐hour average pain severity evaluated on an 11‐point Likert scale. Secondary outcome measures and safety were evaluated. Results.  Compared with placebo‐treated patients, both duloxetine‐treated groups improved significantly more (P < 0.001) on the 24‐hour average pain score. Duloxetine demonstrated superiority to placebo in all secondary analyses of the primary efficacy measure. A significant treatment effect for duloxetine was observed in most secondary measures for pain. Discontinuations due to adverse events were more frequent in the duloxetine 60 mg BID‐ (12.1%) versus the placebo‐ (2.6%) treated group. Duloxetine showed no adverse effects on diabetic control, and both doses were safely administered and well tolerated. Conclusions.  In this clinical trial, duloxetine 60 mg QD and duloxetine 60 mg BID were effective and safe in the management of DPNP.